Kualitas Pelayanan Pembuatan Surat Keterangan Tidak Mampu di Kelurahan Muara Tuhup Kecamatan Laung Tuhup Kabupaten Murung Raya - Farid Zaky Yopiannor; Aditiya Romadhan (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2017)
The purpose of this study was to find out how the Quality of Services for Making Low Tide is Not Affordable in Muara Tuhup Village, Laung Tuhup Subdistrict, Murung Raya Regency. The method used in this study is qualitative. The primary data in this study as informants are employees who provide services and communities in Muara Tuhup Village. Secondary data from materials, both in the form of books, articles, scientific works, newspapers, and scientific journals. Based on the results of the research that the quality of service for making inadequate certificates in the Muara Tuhup Sub-District of Laung Tahup Subdistrict, Murung Raya Regency still has a number of things that have not been maximized from the tangible aspect of service, convenience in the service process, employee discipline, and employee service processes use tools. Furthermore, the reliability of service standards, the ability of employees to use service aids. Additionally, responsiveness (response/response) response or response in response to complaints from service users, service employees have performed services quickly and precisely which has not been maximized, served on time, and all complaints from service users have not been responded to. Furthermore, Assurance (Guarantee) Guarantees timely service